2(m-1)=3(m+1)

Simple and best practice solution for 2(m-1)=3(m+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(m-1)=3(m+1) equation:



2(m-1)=3(m+1)
We move all terms to the left:
2(m-1)-(3(m+1))=0
We multiply parentheses
2m-(3(m+1))-2=0
We calculate terms in parentheses: -(3(m+1)), so:
3(m+1)
We multiply parentheses
3m+3
Back to the equation:
-(3m+3)
We get rid of parentheses
2m-3m-3-2=0
We add all the numbers together, and all the variables
-1m-5=0
We move all terms containing m to the left, all other terms to the right
-m=5
m=5/-1
m=-5

See similar equations:

| 3x+45+9x+51=180 | | -5m+10=-45 | | 4(x-8)=-4-3x | | r=104-20 | | a-8.9/9.4=-4.3 | | 8n-18=5n+7 | | 7p+5(p-5)=8p+7 | | 10(x-15)=7 | | 10(x-15)=-7 | | 1/2−3*a=7/8 | | 4|u+7|-69=-13 | | -2(x+7)=-6x+6 | | 4.3-3.2z=7.3 | | 7/3t=-8/4 | | 1/2−3a=7/8 | | 9/6d=-7/4 | | 30-7x=-6(x-6) | | -3/2+6/7u=-4/3 | | 8x2+200=0 | | 4x2=72 | | 1/2x+1/2x+x-25+x-15+100=540 | | -4-5x=1-6x | | -4(a+2)=24-8a | | 18-1.8x=7.36 | | 2/3*x=1/2+8 | | 18y-14=2(9y-7) | | -2x+4+3x=13 | | 2/3x=1/2+8 | | -8n=8n-8(3n-8) | | 2/9x=-7/5 | | x2=9/484 | | -2x+2=2+x |

Equations solver categories